Improving China’s maritime law enforcement operations against overfishing in the South China Sea—Based on a comparison with the Indonesian law enforcement system against IUU Fishing - Minyou Yu; Weizhe Liu (PLoS ONE, 2025)
Overfishing in the South China Sea has become increasingly severe these years, with Illegal, Unreported, and Unregulated (IUU) fishing being one of the main contributors to this problem. To ensure regional and global food security as well as stability, it is necessary and urgent for the South China Sea coastal states to deal with overfishing effectively. Based on a comparison with the Indonesian law enforcement system against IUU fishing, the paper proposes a path for China to improve its fishery law enforcement system. It also utilizes VIIRS-DNB data analysis to support some viewpoints and highlight areas needing special attention. In the future, China should clarify the legislation, policy, and institutional authority distribution for fishery law enforcement; adopt more effective measures while meeting the necessity requirements of the United Nations Convention on the Law of the Sea; strengthen international cooperation, attempting to reach temporary fishing zone agreements with other coastal states in disputed waters; and involve local fishing communities in the development of the enforcement system.